A Framework for the Selection of Suitable Waste to Energy Technologies for a Sustainable Municipal Solid Waste Management System - Farooq, Ahsan; Haputta, Piyanon; Silalertruksa, Thapat; Gheewala, Shabbir H. (Frontiers in Sustainability, 2021)
Municipal solid waste (MSW) generation has been escalated at a global scale and poses drastic impacts on the environment along with many socio-economic problems. Waste to energy (WtE) technologies have been recognized to convert MSW into useful energy and minimize the problems related to it. This study reviewed different WtE technologies according to the conversion pathways, end-products, and their applications, and assessed statistical values of these technologies based on six different factors, viz., environmental performance, suitable waste fractions, capital and operational cost, efficiency, and complexity of the technology, the skillset of the labor, and favorable geographical location for the plant. The results of this review showed that biochemical and physicochemical WtE technologies are more favorable to convert organic waste, while thermochemical WtE technologies are suitable to process combustible fractions of organic and inorganic MSW. Based on the statistical review of considered factors from the literature, the statistical profiles of concerned WtE technologies were observed. Finally, a general framework in the form of a systematic scheme was proposed for the selection of the most suitable WtE technologies for a sustainable MSW management system. The recommended indicators, methods, and models in the proposed framework were selected after a detailed review of the literature published in well-known scientific journals, and reports of leading international organizations such as the World Bank, International Energy Agency (IEA), and International Labour Organization (ILO). Moreover, the databases to extract the data for the estimation of various recommended indicators have also been presented.